Instabilities and propagation properties in two-component reaction-diffusion systems - Shams Eldeen, Samir (2011)
This thesis deals with a detailed linear analysis for a two-component reaction-diffusion system with constant diffusion coefficients. A comprehensive linear stability analysis results in three types of instabilities: (1) stationary periodic instability, (2) oscillatory uniform and (3) stationary uniform. The first instability involves pattern formation and the other two do not. Precise parameter regimes are identified for each.